The concept of sustanaible development in the globalization of the world economy - Оksana Urban; Мykola Dziamulych; Natalia Chyzh (Економічний форум)
The article examines the main prerequisites of the concept of sustainable development in the context of the globalization of the world economy. In particular, the essence of the term "sustainable development" and related economic categories was analyzed, the main components (social, ecological and economic) and the main orientations of this concept were distinguished. Attention is focused on the relationship between the concept of sustainable development and the theory of capital preservation, which involves distinguishing two types of sustainability - strong and weak. There are many global problems that have an impact on the development of humanity and the biosphere. That is why the work is focused on finding opportunities to minimize the negative impact of global problems on socio-economic network processes. And therefore, the decisive step to the further spread of the concept of sustainable development is regional implementation in accordance with existing local problems. That is why the author's attention will be focused on the study of the circular economy, which involves the transition from the traditional linear model "production - consumption - disposal" to the model "production - consumption - recycling - use". Considerable weight is given to the study of green public procurement (GPP), which is an important tool of the circular economy, which is based on the principle of greening procurement, which is focused, first of all, on the public sector. In many countries, EPAs are already included in national strategies for sustainable development and are mandatory for government bodies and enterprises. It is this feature that is the basis of the structural transformation of the national economy, which involves the selection of an "ecologically destructive" type of economic structure, but with varying degrees of application of appropriate economic and ecological tools. And therefore it should be understood that it is necessary to concentrate attention on the transition from the principles of directive and command planning to indicative and regulatory principles of the development of the domestic economy